1988
DOI: 10.1016/0309-1651(88)90052-5
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of endocytosed proteins is unaltered in senescent human fibroblasts

Abstract: We compared the abilities of young and senescent fibroblasts to take up and degrade [3H]ribonuclease A (native and oxidized), [3H]ribonuclease4-13, [3H]hemoglobin, [3H]glyceraldehyde-3-phosphate dehydrogenase, [3H]beta-galactosidase, [3H]glycogen phosphorylase, and [125I]serum albumin. The endocytic uptake of these proteins ranged from fluid-phase to predominantly absorptive. Intralysosomal degradation rates of the different endocytosed proteins varied by an order of magnitude, but in no case was there a diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0

Year Published

1989
1989
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 19 publications
2
2
0
Order By: Relevance
“…The degradation of this desialyated glycoprotein was similar in hepatocytes isolated from the three groups of mice. This observation is consistent with the report by Gurley and Dice (113) showing that the rate of degradation of endocytosed proteins was similar in early-and latepassage human fibroblasts.…”
Section: Effect Of Age On the Degradation Of Specific Proteinssupporting
confidence: 93%
“…The degradation of this desialyated glycoprotein was similar in hepatocytes isolated from the three groups of mice. This observation is consistent with the report by Gurley and Dice (113) showing that the rate of degradation of endocytosed proteins was similar in early-and latepassage human fibroblasts.…”
Section: Effect Of Age On the Degradation Of Specific Proteinssupporting
confidence: 93%
“…Nevertheless, neither the maturation nor the degradation capabilities of vesicles were affected. Our findings support the conclusion of Gurley and Dice that there are no differences in the intralysosomal degradation rates of several endocytosed proteins between young and senescent fibroblast cells (Gurley and Dice, 1988). On the other hand, there are reports that senescent cells undergo receptor-mediated endocytosis changes (Park et al, 2001b;Park et al, 2002).…”
Section: Discussionsupporting
confidence: 92%
“…To determine how much mAb 13D3 would be needed to neutralize ly-hsc73, we radiolabeled mAb 13D3 with NaB 3 H 4 and determined the amount of [ 3 H]mAb 13D3 that could be endocytosed by fibroblasts and its half-life after endocytosis. These studies indicated that mAb 13D3 was internalized by absorptive endocytosis at 12 times the rate of [ 3 H]sucrose, a fluid-phase marker (Gurley and Dice, 1988), and it had a half-life within lysosomes of 45 h (data not shown). The previous quantitation of the amount of ly-hsc73 (Terlecky and Dice, 1993) allowed us to calculate that overnight endocytosis of 10 g/ml of mAb 13D3 should result in an eightfold molar excess of mAb 13D3 over ly-hsc73.…”
Section: Role Of Ly-hsc73 In the Hsc73-stimulated Lysosomal Proteolytic Pathwaymentioning
confidence: 97%